Analysis of interactions between telomeric i-motif DNA and a cyclic tetraoxazole compound - Shadi Sedghi Masoud (2020)
The interaction of a macrocyclic tetraoxazole compound, L2H2-4OTD (1), with two aminoalkyl side chains and telomeric i-motif, was investigated by means of electrophoretic mobility shift assay, circular dichroism spectroscopy, mass spectrometry and NMR spectroscopy analyses. The results indicate that 1 interacts with the i-motif structure at two preferred binding sites.